Overall Rebalancing of Gut Microbiota Is Key to Autism Intervention - Lu, Chang; Rong, Jiaqi; Fu, Changxing; Wang, Wenshi; Xu, Jing; Ju, Xing-Da (Frontiers in Psychology, 2022)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder with unclear etiology, and due to the lack of effective treatment, ASD patients bring enormous economic and psychological burden to families and society. In recent years, many studies have found that children with ASD are associated with gastrointestinal diseases, and the composition of gut microbiota (GM) is different from that of typical developing children. Thus, many researchers believe that the gut-brain axis may play an important role in the occurrence and development of ASD. Indeed, some clinical trials and animal studies have reported changes in neurological function, behaviour, and comorbid symptoms of autistic children after rebalancing the composition of the GM through the use of antibiotics, prebiotics, and probiotics or microbiota transfer therapy (MMT). In view of the emergence of new therapies based on the modulation of GM, characterizing the individual gut bacterial profile evaluating the effectiveness of intervention therapies could help provide a better quality of life for subjects with ASD. This paper reviews current studies on interventions to rebalance the GM in children with ASD. The results showed that Lactobacillus plantarum may be an effective strain for the probiotic treatment of ASD. However, the greater effectiveness of MMT treatment suggests that it may be more important to pay attention to the overall balance of the patient's GM. Based on these findings, a more thorough assessment of the GM is expected to contribute to personalized microbial intervention, which can be used as a supplementary treatment for ASD.